PENGARUH TERAPI MUSIK KLASIK TERHADAP TINGKAT STRES PADA LANSIA - Ilta Marlena; Sherly Widianti; Bela Purnama Dewi (LPPM STIKes Mitra Adiguna, 2026)
Stress is a common psychological problem experienced by the elderly as a result of the physical, psychological, and social transformations that occur during the aging process. If stress is left untreated, it can significantly reduce their overall quality of life. This study was conducted to examine how classical music therapy affects stress levels in the elderly at the Bina Sejahtera Elderly Health Post in Palembang. The study used a pre-experimental design with a single-group pretest-posttest methodology. A total of 35 elderly participants were recruited through a total sampling technique. Stress levels were assessed using a questionnaire administered before and after the classical music therapy intervention. Data normality was evaluated using the Shapiro-Wilk test, which indicated a normal distribution. Furthermore, bivariate analysis was conducted using a paired-sample t-test. The results showed a statistically significant reduction in stress levels in the elderly after the classical music therapy intervention, with a p-value of 0.000, less than 0.05. This study concludes that classical music therapy is effective in reducing stress levels in the elderly and can serve as a valuable non-pharmacological approach in elderly healthcare.